The Translation of Horace’s Odes by Andreas Heinrich Bucholtz - Gutsche, Victoria (Collections and Books, Images and Texts: Early Modern German Cultures of the Book, 2023)
In 1639 Andreas Heinrich Bucholtz published the first German translation of the Odes of Horace. Against the background of contemporary translation practice, it becomes apparent that Bucholtz primarily follows Martin Opitz in conceiving of translation as a poetic act. He considers his translations to be interpretive replicas, which primarily serve the purpose of exploring the poetic capabilities of the German language, in addition to attempting to establish its status as a literary language.<br